Településhálózat-fejlesztés és településrendezés Romániában - Hunya, Gábor (Tér és Társadalom, 1989)
In March 1988 the secretary general of the Romanian Communist Party announced an overall program for village network development and village planning („sistematizarea") which sentenced 8000 villages to liquidation. Later, due to international protest, the plan of destruction was not mentioned by the Romanian propaganda but it was not rejected either. The present paper deals with the background of this program, its historical and conceptual antecedents and its relationship with the program of agricultural development. Within the strongly centralized system of decision making in Romania where a citizen must not freely decide where to live or work where family house construction is hardly licensed, where generations are confined to move into blocks of buildings, it is hard to imagine anything else than a strongly selective development policy which favours large settlements. Units of agricultural production are also concentrated, possibilities for individual and household farming are limited. This development model follows Soviet ideas of the late 1950s which gained adherents all over Eastern Europe but when the drawbacks of overconcentration in production and in settlernent development were becoming obvious, this model was more or less rejected. The acts of 1968 and 1974 on settiement network development were the antecedents of the above mentioned program in Romania. A project of developing small towns, included in these acts, was struck off from the agenda in the mid-1970s then it cropped up again in 1986. From a study of the Romanian village network it emerges that the planned tiny villages can be found on the southern slopes of the Carpathians. Nevertheless, it was not here where the execution of the program started, but it did around Bucharest and in four-five model villages in each county. All forms of modernization, but particularly socialist industrialization which is controlled from the top and striving for prompt results, find themselves opposed with endeavours to preserve local communities. The nationalization („etatization") of society is gaining larger and larger dimensions and the possibilities of individual life are getting ever smaller in Romania in the 1980s. Earlier the peasantry was mainly exploited by economic means – the reorganization of its home place is a new phenomenon.